Historical and pedagogical aspects of foreign language education in Ukraine (Educational Dimension, 2023)
The article is devoted to considering historical and pedagogical aspects of the development of foreign language education in Ukraine, starting from ancient times and up to our time. The definition and analysis of “foreign language education” as a multifaceted phenomenon, which includes several processes: cognition, development, education and training, is provided. Foreign language education is linguistic and cultural education, the result of which should be a plurilingual personality. It is noted that foreign languages were studied in our country even before the adoption of Christianity. For centuries, education and all other socio-political processes were taken care of by the church; therefore, Church Slavonic and Greek languages were studied in schools due to their confessional status. Various educational institutions (“fraternal schools”, “multilingual”, “German”, and “Latin” schools) were opened, in which teaching in foreign languages was widespread. Latin has always held a high status not only as a foreign language but also as a language of instruction in many disciplines. It turns out that domestic foreign language education has been implemented for many years depending on the language policy of the ruling power structures in one or another territory of our country. This affected the main trends and challenges that made it necessary to focus on preserving one’s language and culture. The development of new economic and social processes influenced the departure from “dead languages” to studying “living” ones, which had specific practical significance. It was revealed that the opening of three universities, Kharkiv, Kyiv and Novorossiysk, which taught both classical languages (Latin and ancient Greek) and new ones (French, German, Italian, Polish and English), was a breakthrough in the development of foreign language teaching in higher education. It has been established that after the declaration of independence of Ukraine in 1991, foreign language education developed under the influence of important state documents of Ukraine regarding the study of foreign languages by citizens and the All-European recommendations on language education: study, teaching, evaluation. Therefore, the changes that are taking place force us to rethink the previous experience and integrate new progressive ideas into the educational process in accordance with the strategy for the development of foreign language education in our country.
Keywords: Ukraine; foreign language education; foreign languages; culture; history of foreign language education; schools teaching different foreign languages